PENGARUH KOMPENSASI DAN KOMITMEN ORGANISASI TERHADAP SEMANGAT KERJA KARYAWAN PADA HOTEL DYAN GRAHA PEKANBARU - Sipahutar, Dina Wiranti; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much compensation and organizational commitment to employee morale. The sample in this study was taken as many as 54 respondents and the technique used was Total Sampling. The data in this study used the survey method through questionnaires filled out by employees. The research method used is simple regression analysis, multiple regression analysis, simultaneous and partial analysis of the coefficient of determination, and hypothesis testing namely F test and T test. The result of this study indicate compensation has a significant effect on employee morale. Organizational Commitment has a significant effect on employee morale. And simultaneously compensation and organizational commitment have a significant effect on employee morale. Further research is recommended to use other methods in examining employee morale, for example through in-depth interviews with respondents. Keywords: Compensastion, Organizational Commitment and Employee                                 Spirit/Morale